2022
DOI: 10.7759/cureus.28759
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Harmonic Scalpel Versus Conventional Techniques of Appendiceal Stump Closure in Laparoscopic Appendicectomy

Abstract: Acute appendicitis is one of the most commonly encountered surgical emergencies worldwide. The laparoscopic approach for managing acute appendicitis is gaining popularity over open appendicectomy in the current surgical practice. The advantages of laparoscopic appendectomy are early recovery, fewer wound complications, less pain and better cosmesis. One of the most critical steps in laparoscopic appendicectomy is a secure appendicular stump closure. Life-threatening postoperative complications are often encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In contrast, total drainage of the back increased in the HA group from a median of 1543.9 mL (260-1115 mL) to 1669.8 mL (90-985 mL); however, this difference was not statistically significant. The HA group showed no difference in the duration of drain placement in the back [median, EC 12.0 (10-14) versus HA 12.3 (10)(11)(12)(13)(14) days] and in the anterior chest [median, EC 6.3 (4-8) versus HA 5.9 (4-8) days].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, total drainage of the back increased in the HA group from a median of 1543.9 mL (260-1115 mL) to 1669.8 mL (90-985 mL); however, this difference was not statistically significant. The HA group showed no difference in the duration of drain placement in the back [median, EC 12.0 (10-14) versus HA 12.3 (10)(11)(12)(13)(14) days] and in the anterior chest [median, EC 6.3 (4-8) versus HA 5.9 (4-8) days].…”
Section: Resultsmentioning
confidence: 99%
“…This technique is expected to minimize collateral damage because it minimizes energy transfer to the surrounding tissue. 9 , 10 Ultrasonic scalpels have recently been reported to be useful in preventing seroma in mastectomies. 11 Additionally, a study using the Harmonic Focus+ Shears in LD flap reconstruction found that compared with electrocautery, the Harmonic Focus+ Shears were associated with reduced seroma formation, shorter drainage period operative time, and hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review concluded that in terms of the length of stay and postoperative complications, such as wound infection or postoperative ileus, a harmonic scalpel is similar. It has the only advantage of reducing the duration of the operation in comparison with conventional laparoscopic appendectomy techniques [ 13 ]. The main drawback of the harmonic scalpel is the price of disposable hand equipment [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has the only advantage of reducing the duration of the operation in comparison with conventional laparoscopic appendectomy techniques [ 13 ]. The main drawback of the harmonic scalpel is the price of disposable hand equipment [ 13 ]. However, there is no consensus on the technical method for closing the appendix stump.…”
Section: Introductionmentioning
confidence: 99%